Religioznoe obrazovanie v gosudarstvennych srednich školach: Teorija, metodologija i praktika. = Religious Education in Public Secondary Schools: Theory, Methodology and Praxis - Proshak, Vitaliy (Bogoslovskie razmyšlenija, 2018)
Religion, also in its educational dimension, is an essential component of contemporary society. The present article Religious Education in Public Secondary Schools: Theory, Methodology and Praxis is an attempt to define religious education in public secondary school context in connection to its theory, methodology and praxis. An overview of the existing theories and methods of religious education is presented in the article on the base of the research works of Jeff Astley, Cok Bakker, Thomas H. Groom, Robert Jackson, Siebren Miedema, Gabriel Moran, John Sealey and others. The final part of the article introduces reader to a variety of praxis of religious education in Europe as described by Jean-Paul Willaime and Vitaliy V. Proshak. Analyzing European praxis in relation to religious education, author concludes that treatment of religious education by state could testify about democracy development of the state itself.In this article author uses the term ‘religious education’ in its inclusive definition that could be applicable to all confessional/ religious dimensions of education. The focus of the article is not on the religious/ confessional character or differences in education, but on the general theory, methodology and praxis in relation to religion and education in the context of secondary school.